Disabling hand injuries in boxing: Boxer's knuckle and traumatic carpal boss - Melone, C. P.; Polatsch, D. B.; Beldner, S. (Clinics in Sports Medicine, 2009)
This article describes the treatment of the two most debilitating hand-related boxing injuries: boxer's knuckle and traumatic carpal boss. Recognition of the normal anatomy as well as the predictable pathology facilitates an accurate diagnosis and precision surgery. For boxer's knuckle, direct repair of the disrupted extensor hood, without the need for tendon augmentation, has been consistently employed; for traumatic carpal boss, arthrodesis of the destabilized carpometacarpal joints has been the preferred method of treatment. Precisely executed operative treatment of both injuries has resulted in a favorable outcome, as in the vast majority of cases the boxers have experienced relief of pain, restoration of function, and an unrestricted return to competition.